Factor affecting tax compliance among online business SMEs - Ismail, Amir Salim (2022)
This study aims to examine the level of tax compliance among online business in Malaysia who conduct business at the micro level SMEs. This qualitative study was conducted to obtain an in-depth view from online traders in the sole proprietorship category in Malaysia. This studyuses factors that are often used to see the level of tax compliance, namely tax knowledge, tax compliance costs, tax complexity and poor record keeping. Five sole proprietor category onlinebusiness who run micro businesses around the Klang Valley were selected as a study sample and telephone interviews were used as research instruments. As a result of the findings of the study, it can be concluded that the respondents have basic tax knowledge and they hope that this knowledge of taxation can be provided more to businesses or taxpayers who are new to submitting tax forms for the first time. Basically, the cost of tax compliance and tax complexity is still acceptable to them and the role of tax agent helps them is undeniable. For the poor records keeping, respondents expect a simple and easy-to-practice mechanism to be found in order to facilitate their taxation affairs and at the same time smoothen the affairs of tax audits on them. Additional research is recommended to examine current taxation education to see the level of effectiveness of such education on sole proprietors who run online businesses compliance.